Spectral Purity Improvement by Combining Self-Injection Locking and Stimulated Thermal Rayleigh Scattering in Fiber Lasers - Hong Dang; Kunpeng Feng; Jiwen Cui; Yuanhang Zhang; Xun Sun; Wenlei Yang; Jiubin Tan (IEEE Photonics Journal)
A stimulated thermal Rayleigh scattering (STRS)-based self-injection locking technique is proposed and utilized in fiber laser to improve its spectral purity. Both theoretical and experimental analyses of the STRS-based filter and the interaction mechanism between the STRS-based filter and self-injection locking are demonstrated in detail. These analyses verify effects of the proposed method on single-longitudinal-mode (SLM) selection and linewidth compression. A fiber laser employing STRS-based self-injection locking configuration is designed, and a significant improvement of spectral purity comparing to commercially available lasers is achieved. Experimental results indicate that this fiber laser operates at SLM regime and has a linewidth of 45 Hz, and can be widely applied in distributed sensing, optical communication, and high-resolution optical spectrum analysis.